A comparative analysis between on-site work, hybrid work, and remote work - Monnerat, Rafaela (2023)
This dissertation has as its objective to make a comparative analysis between on-site work to the new and ascending work models, Remote and Hybrid. These models of work have become a reality across the world after the outburst of the Pandemic of Covid-19. Even after the Pandemic was contained, many companies around the globe kept the new models of work as a new reality. There are still a lot of divergent ideas and very little time with the new reality, to have definitive opinions about the positive and negative aspects of on-site work, Remote work, and Hybrid work models. To compare the different work models, this research analyzes a wide selection of articles that approach the subject and present different views and data about it. Based on the literature and research, hypothesis and research questions were created to build a survey. The survey was done with a sample of 80 individuals, the majority in Portugal and Brazil. Based on it, it was possible to analyze the opinion of many employees and employers that work in different models and evaluate the different opinions about them. With the questionnaire and analysis of the results, it was possible to conclude that in a general framework, remote and hybrid work is dominating the labor market in the realities of the individuals in the sample, the positive aspects are greater than the negative ones and the workers mostly prefer to work in the new work models, and believe that they will be part of the future.